The role of front electrodes and intermediate reflectors in the optoelectronic properties of high-efficiency micromorph solar cells - Dominé, Didier (My University, 2009)
On the road towards silicon thin-film photovoltaic modules with a conversion efficiency of 10%, the micromorph tandem solar cell is a promising candidate. Two ingredients are commonly used for light-management within the micromorph solar cell: (1) nano-textured interfaces and (2) insertion of an intermediate reflector in-between the two component cells of the tandem. The purpose of the nano-textures is to promote light scattering at the optical interfaces and therefore to increase the probability of absorption of red light in the amorphous silicon (a-Si:H) absorber of the top cell and of infrared light in the microcrystalline silicon (µc-Si:H) absorber of the bottom cell. For micromorph devices deposited on glass plates, these nano-textures are obtained by the deposition of the solar cell on a surface-textured transparent conductive front electrode. The function of the second ingredient, the intermediate reflector, is to increase the photo-current density within the a-Si:H top cell, thanks to reflections produced at the additional optical interface. This document study the interplay between those two ingredients within the optoelectronic system formed by the micromorph solar cell. In particular, the impact of the surface morphology of the front contact on the growth and performances of µc-Si:H solar cells is described. A study of the electronic transport within µc-Si:H cells is carried out using Scanning Kelvin probe microscopy and two original methods based on conductive atomic force microscopy. Also, the importance of the angular distribution of the light scattered by nano-textured front electrodes is demonstrated. Angular distributions for light scattered in-air and in a-Si:H are calculated from atomic force microscopy pictures of different front electrodes. The calculations are performed using phase screens and the scalar scattering theory. Theoretical results obtained with this approach are successfully confronted with experimental data obtained in-air. Besides, a quantitative comparison of the relative importance of a reduced free carrier absorption (FCA) in the front electrode and of an improvement of its light-trapping capability is presented. For the different types of front contacts used in this work, this comparison shows that the reduction of FCA produces more than 50% of the gains in photo-current density. Regarding the direct effect of the intermediate reflector, this work experimentally demonstrates that the gain obtained in the current density of the top cell is larger with nano-textured interfaces than with flat interfaces. An experimental gain up to 2.8 mA/cm2 is achieved here. With respect to device optimization, the best initial conversion efficiency achieved in this work is 13.3% for a 1.2 cm2 micromorph cell deposited on a glass plate with an anti-reflection (AR) coating, yielding the remarkably high value of 13.8 mA/cm2 for the short-circuit current density. The best stabilized device achieved in this work yields 11.1% stabilized conversion efficiency (1.2 cm2 and no AR coating)
Thèse de doctorat : Université de Neuchâtel, 2009 ; Th. 2134
Keywords: cellules solaires en couches minces de silicium; silicium amorphe; silicium microcristallin; micromorphe; réflecteur intermédiaire; oxyde conducteur transparent; surfaces nano-texturées; piégeage de la lumière; théorie scalaire de la diffusion; microscopie à force atomique en conduction; microscopie à sonde de Kelvin; silicon thin-film solar cells; amorphous silicon; microcrystalline silicon; micromorph; intermediate reflector; transparent conductive oxide; nano-textured surfaces; light trapping; scalar scattering theory; conductive atomic force microscopy; scanning Kelvin probe microscopy